1993
DOI: 10.1002/joc.3370130805
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnections between North Pacific SST anomalies and growing season extended dry spells on the canadian prairies

Abstract: This investigation documents the relationships between anomalous North Pacific sea-surface temperatures (SSTs) and the occurrence of growing season extended dry spells on the Canadian Prairies. Results show a significant correlation between extended dry spells and a positive SST anomaly gradient in the east-central North Pacific. The gradient exists between an area of anomalously cold water in the east-central North Pacific in the area 30"N40°N latitude and 165"W-l35"W longitude, and an area of anomalously war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
(19 reference statements)
2
42
0
Order By: Relevance
“…Conversely, the positive phase of PC1 is associated with negative SST anomalies along the west coast of North America and southern Canada (−0.2 to −0.6°C), positive SST anomalies in the central Pacific and along the coast of Alaska (+0.2 to +0.6°C), and negative SST anomalies in the northwestern Pacific (−0.2 to −0.4°C) (Figure 15(b)). Other researchers have found that anomalously dry/wet conditions in the Canadian prairies are associated with similar patterns of North Pacific SST anomalies (Bonsal et al, 1993;Hsieh et al, 1999). It is likely that both tropical and North Pacific SST anomalies contribute to the occurrence of anomalous June-July moisture conditions in the Canadian prairies.…”
Section: Relationship Between Anomalous June-july Moisture Conditionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Conversely, the positive phase of PC1 is associated with negative SST anomalies along the west coast of North America and southern Canada (−0.2 to −0.6°C), positive SST anomalies in the central Pacific and along the coast of Alaska (+0.2 to +0.6°C), and negative SST anomalies in the northwestern Pacific (−0.2 to −0.4°C) (Figure 15(b)). Other researchers have found that anomalously dry/wet conditions in the Canadian prairies are associated with similar patterns of North Pacific SST anomalies (Bonsal et al, 1993;Hsieh et al, 1999). It is likely that both tropical and North Pacific SST anomalies contribute to the occurrence of anomalous June-July moisture conditions in the Canadian prairies.…”
Section: Relationship Between Anomalous June-july Moisture Conditionsmentioning
confidence: 79%
“…PC1: composite June-July tropical Pacific SST anomalies (°C) associated with (a) the negative phase (anomalously dry; composite of June-July 1961, 1988, 1967, 1977 and (b) the positive phase (anomalously wet; composite of June-July 1993, 1953, 1991 of warm SST anomalies is present in the Gulf of Alaska and along much of the west coast of North America (+0.2 to +0.8°C), a pool of cool SST anomalies in the central Pacific (−0.2°C), and a large pool of warm SST anomalies in the western Pacific (+0.2 to +0.6°C). It is believed that this pattern of SST anomalies may help to reinforce (sustain) the ridging conditions over the study region (Bonsal et al, 1993). Conversely, the positive phase of PC1 is associated with negative SST anomalies along the west coast of North America and southern Canada (−0.2 to −0.6°C), positive SST anomalies in the central Pacific and along the coast of Alaska (+0.2 to +0.6°C), and negative SST anomalies in the northwestern Pacific (−0.2 to −0.4°C) (Figure 15(b)).…”
Section: Relationship Between Anomalous June-july Moisture Conditionsmentioning
confidence: 90%
“…It has been widely illustrated that interactions between coupled ocean-atmosphere systems can lead to large-scale changes in climate and air mass circulation (e.g., Minobe, 1997;Nigam et al, 1999;Barlow et al, 2001). The large inertia of the oceans can lead to persistence of such anomalies for multi-decadal time periods leading to meso-scale reorganization of climate (Ropelewski and Jones, 1987;Bonsal et al, 1993;Zhang et al, 1997). Within the Pacific basin, sea surface temperatures (SSTs) have been identified as a primary driver of climate throughout western North America across multiple time scales (Namais and Cayan, 1981;Trenberth et al, 1988;Case and MacDonald, 1995;Woodhouse and Overpeck, 1998;Cayan et al, 1999;Graumlich et al, 2003;MacDonald and Case, 2005;Cook et al, 2007;MacDonald, 2007).…”
Section: Climatic Drivers Of Precipitation In the Yellowknife Regionmentioning
confidence: 99%
“…Bonsal et al (1993) found a significant relationship between persistent SST anomalies in the North Pacific Ocean and extended dry spells over the Canadian Prairies during the growing season of May-August. The severity of the dry spells was defined by their duration, spatial extent, and strength of the 500 hPa anomalies over the Prairies.…”
Section: Introductionmentioning
confidence: 95%